Vibration fatigue by spectral methods : from structural dynamics to fatigue damage : theory and experiments /: from structural dynamics to fatigue damage : theory and experiments. (2020) - Slavic, Janko; Boltezar, Miha; Mrsnik, Matjaz; Cesnik, Martin; Javh, Jaka
No abstract available